Playful work design and thriving in academia: the mediating role of work-related flow - Ahmed M. Elsayed; Ibrahim G. Mahgoub; Mahmoud Abdelaziz Ahmed Abdelaziz (BMC Psychology)
Abstract Background Based on the Socially Embedded Model of Thriving (SEMT), the present study extends research on thriving by examining the effect of a new bottom-up approach to work design, playful work design (PWD), on thriving at work. Furthermore, we try to improve our understanding of the PWD-thriving relationship by examining the mediating role of work-related flow. Method A multi-temporal questionnaire data collection approach was adopted, conducted across two waves with an interval of two weeks. At Time 1, 341 participants completed questionnaires measuring Playful Work Design and Work-related Flow. At Time 2, 309 participants responded to the thriving questionnaire. Data were analyzed using WarpPLS 8.0 software. Results Findings reveal that PWD has a significant direct impact on both work-related flow and thriving at work. Work enjoyment and motivation partially mediated the relationship between PWD and thriving, whereas work absorption did not show a statistically significant mediating effect. Conclusions The study provides fresh empirical insights into the psychological mechanisms linking PWD to thriving, particularly within underexplored academic settings. It contributes to the literature by highlighting the role of enjoyment and motivational pathways in fostering thriving among academics and suggests practical implications for enhancing faculty thriving and well-being in higher education institutions.